Penerapan Sistem Akuntansi dengan Nota Manual di Perusahaan Konveksi - Bambang Setyobudi Irianto; Saniyya Nabila Su’daa (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
An accounting system is an essential business tool for companies. BBR Company is a garment manufacturing enterprise that needs to develop an accounting system to support its operational activities. This community service program focuses on the development and implementation of an accounting system at BBR Company. Through the application of a manual invoice-based accounting system, it is expected that the business unit will be able to manage its operations more effectively. Consequently, this implementation is expected to improve the company’s overall performance.